Study on MRI Changes in Phenylketonuria in Patients Referred to Mofid Hospital/Iran - KARIMZADEH, Parveneh; AHMADABADI*, Farzad; JAFARI, Narjes; SHARIATMADARI, Fakhreddin; NEMATI, Hamid; AHADI, Adel; KARIMI DARDASHTI, Sanaz; MIRZARAHIMI, Mehrdad; DASTBORHAN, Zahra; ZARE NOGHABI, Javad (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Karimzadeh P, Ahmadabadi F, Jafari N, Shariatmadari F, Nemati H, Ahadi A, Karimi Dardashti S, Mirzarahimi M, Dastborhan Z, Zare Noghabi J. Study on MRI Changes in Phenylketonuria in Patients Referred to Mofid Hospital. Iran J Child Neurol. 2014 Spring 8(2):53-56. Objective Phenylketonuria is one of the most common metabolic disorders and the first known cause of mental retardation in pediatrics. As Screening for phenylketonuria (PKU) is not a routine neurometabolic screening test for neonates in Iran, many PKU cases may be diagnosed after developing the clinical symptoms. One of the findings of PKU is myelination disorders, which is seen as hypersignal regions in T2-weighted (T2W) and FLAIR sequences of brain MRI. The aim of our study was to assess MRI changes in PKU patients referred to Mofid Children’s Hospital, 2010-2011. Materials & Methods We studied all PKU cases referred to our clinic as a referral neurometabolic center in Iran for brain MRI and assessed the phenylalanine level at the time of Imaging. The mean phenylalanine level (in one year), clinical manifestations, and MRI pattern based on Thompson scoring, were evaluated. Results The mean age of our study group was 155±99 months and the mean diagnosis age was 37±27.85 months. There were 15 patients with positive and 15 with negative family history. The mean phenylalanine level at the time of imaging was 9.75±6.28 and the mean 1 year phenylalanine level was 10.28±4.82. Seventy percent of our patients had MRI involvement, in whom 20% showed atrophic changes, in addition to white matter involvement. Based on modified Thompson scoring, the score for our study group was 4.84. The maximum involvement in MRI was in occipital region, followed by parietal, frontal, and temporal zones. There was not any correlation between MRI score and patients’ age. But we found significant relationship between MRI score and the age of regimen cessation. No correlation was seen between phenylalanine level (at the time of Imaging) and MRI score. But there was a relationship between mean 1 year phenylalanine level and MRI score. Conclusion According to the results of this study, brain MRI and white matter involvement can be used for evaluation of long-term control of phenylalanine level in PKU cases. References 1. Blau Nenad. Phenylketonuria and BH4 Deficiencies. London: UNI-MED; 2010. 2. Buck PS. The child who never grew. Woodbine House; 1992. 3. Rezvani I, Melvin JJ. Defects in metabolism of amino acids. In: Kliegman RM, Stanton BF, St. Geme J, Behrman RE, editors. Nelson Textbook of Pediatrics. 19th ed. USA: Elsevier; 2011. p. 418-22. 4. Menkes J, Wilcox WR. Inherited Metabolic Diseases of nervous system. In: Menkes JH, editor Child neurology. 7th ed. Philadelphia: Lippincott Williams&Wilkins; 2006. p. 34-36. 5. Aicardi J. Diseases of the nervous system in childhood. London: Mac Keith press; 2009. 6. Enns GM, Cowan TM, Klein O, Packman S. Aminoacidemias and organic acidemias. In: Swaiman KF. Swaimans Pediatric Neurology principle and practice. 5th ed. China: Saunders; 2012. p. 330-7. 7. Barkovich J. Toxic and Metabolic Brain disorders. In: Barkovich J, editor Pediatric Neuroimaging. 4th ed. USA: Lippincott William&Wilkins;2005. p. 88-92. 8. Van der knaap MS. Phenylketonuria. In: Van der knaap MS, Valk J, editor. Magnetic resonance of Myelination and Myelin Disorders. 3rd ed. Germany: Springer; 2005. p. 285-90. 9. Manara R, Burlina AP, Citton V, Ermani M, Vespignani F, Carollo C, et al. Brain MRI diffusion-Weighted imaging in patients with classical phenylketonuria: Neuroradiology (2009)51:803-12. 10. Möller HE, Weglage J, Bick U, Wiedermann D, Feldmann R, Ullrich K. Brain imaging and proton Magnetic Resonance Spectroscopy in Patients with Phenylketonuria Pediatrics 2003;112(6 Pt 2):1580-3. 11. Phillips MD, McGraw P, Lowe MJ, Mathews VP, Hainline BE. Diffusion-Weighted Imaging of White Matter Abnormalities in Patients with Phenylketonuria. AJNR Am J Neuroradiol 2001 Sep;22(8):1583-6. 12. Cleary MA, Walter JH, Wraith JE, Jenkins JP, Alani SM, Tyler K, et al. Magnetic resonance Imaging of the Brain in Phenyl ketonuria. Lancet 1994;344(8915):87-90.